PERCEPTION OF THE LECTURE GENRE BY GENERATION Z STUDENTS (BASED ON ASSOCIATIVE EXPERIMENT) - Daria D. Starikova; Ksenia D. Voytsekh; Daria D. Lozhkina; Lada A. Selina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2025)
The article is devoted to the analysis of the perception of the lecture genre from the standpoint of cognitive linguistics and psycholinguistics aimed to describe the features of the reception of this genre in various groups of Generation Z representatives. The speech genre in the framework of the conducted study is understood as a special type of mental scheme, a frame, that regulates the speech behaviour and strategies of understanding communicants in similar communication situations. The leading research method is an associative experiment aimed at identifying the specifics of lecture genre perception by two groups of respondents: university applicants and students. The subjects were asked to respond to the verbal stimuli: students to “lecture”, and students and applicants to an “ideal lecture”. Based on the reactions obtained, cognitive classifiers of the Lecture and Ideal Lecture frames were identified and ranked by their intensity recurrence. As a result of interpreting the experimental data, it was found that representatives of Generation Z mostly have negative experience of listening to lecture courses or negative expectations associated with lecture classes; they reject the passive communicative position of the listener and prefer a dialogue with the teacher; the relevance of the information presented in the lecture, the clarity of its presentation and visualisation are significant for respondents. The main classifier of the Ideal Lecture frame changes depending on the group of respondents: for applicants this classifier is information content, while for students it is the contact with the teacher and classmates. The results of the study can be used by university teachers so as to create new lecture courses and modernize the existing ones, as well as to find application in methodological recommendations and advanced training programmes.